2022
DOI: 10.3389/fnins.2022.817067
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Analysis Suggests No Associations of Herpes Simplex Virus Infections With Multiple Sclerosis

Abstract: Previous studies have suggested an association between infection with herpes simplex virus (HSV) and liability to multiple sclerosis (MS), but it remains largely unknown whether the effect is causal. We performed a two-sample Mendelian randomization (MR) study to explore the relationship between genetically predicted HSV infection and MS risk. Genetic instrumental variables for diagnosed infections with HSV (p < 5 × 10–6) were retrieved from the FinnGen study, and single nucleotide polymorphisms associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…With the exponential growth and widespread availability of genotype data, Mendelian randomization (MR) diminishes confounding, strengthens exposure‐outcome associations, and avoids the reverse causalities approach as an epidemiologic study designed to establish a basis between exposures and outcomes 23 . More importantly, the method has been used as a valid tool to study causal relationships of SLE or HSV with several other factors 24–27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exponential growth and widespread availability of genotype data, Mendelian randomization (MR) diminishes confounding, strengthens exposure‐outcome associations, and avoids the reverse causalities approach as an epidemiologic study designed to establish a basis between exposures and outcomes 23 . More importantly, the method has been used as a valid tool to study causal relationships of SLE or HSV with several other factors 24–27 …”
Section: Introductionmentioning
confidence: 99%
“…23 More importantly, the method has been used as a valid tool to study causal relationships of SLE or HSV with several other factors. [24][25][26][27] We estimated the causality of these associations with twosample MR (TSMR) analysis by leveraging summary-level data from extensive genome-wide association studies (GWASs) of HSV infection and SLE risk. It has been reported that only IgG and its Fc portion showed an increased binding rate to HSV-infected cells compared to the uninfected control cells, and other structurally related beta2 microglobulin and other human immunoglobulins like IgM did not exhibit any change in their levels.…”
Section: Introductionmentioning
confidence: 99%
“…MR adopts germline genetic variants as proxies. Because environmental factors and disease processes have no effect on genetic variants, MR can reduce the influence of other factors, enhance the exposure-outcome relationship, and remove reverse causality ( 20 ). It is thought to be a reliable method for circumventing the limits of observational studies by employing genetic variation as an instrumental variable and large-scale data from GWASs ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The causal involvement of HSV virus infection has been investigated by Zhang et al (2022), based on the hypothesis of its involvement in the pathogenesis of MS. HSV, in fact, could invade the CNS, and its presence was found in brain demyelinating plaques of MS patients by analysing post‐mortem tissue (Sanders et al, 1996). However, conflicting observational studies did not find any relationship between HSV infection and MS risk, such as Etemadifar et al (2019) and Koros et al (2014).…”
Section: Resultsmentioning
confidence: 99%